SPEED: an integrated, smartphone-operated, handheld digital PCR Device for point-of-care testing - Zhang, Haoqing; Liu, Xiaocheng; Wang, Xinlu; Yan, Zhiqiang; Xu, Ying; Gaňová, Martina; Řezníček, Tomáš; Korabečná, Marie; Neuzil, Pavel (Microsystems & nanoengineering, 2024)
This study elaborates on the design, fabrication, and data analysis details of SPEED, a recently proposed smartphone-based digital polymerase chain reaction (dPCR) device. The dPCR chips incorporate partition diameters ranging from 50 μm to 5 μm, and these partitions are organized into six distinct blocks to facilitate image processing. Due to the superior thermal conductivity of Si and its potential for mass production, the dPCR chips were fabricated on a Si substrate. A temperature control system based on a high-power density Peltier element and a preheating/cooling PCR protocol user interface shortening the thermal cycle time. The optical design employs four 470 nm light-emitting diodes as light sources, with filters and mirrors effectively managing the light emitted during PCR. An algorithm is utilized for image processing and illumination nonuniformity correction including conversion to a monochromatic format, partition identification, skew correction, and the generation of an image correction mask. We validated the device using a range of deoxyribonucleic acid targets, demonstrating its potential applicability across multiple fields. Therefore, we provide guidance and verification of the design and testing of the recently proposed SPEED device.
Keywords: Microfluidics; Electrical and electronic engineering